Associations between job strain and the cortisol/DHEA-S ratio among management and nonmanagement personnel - Gadinger, Michael C.; Loerbroks, Adrian; Schneider, Sven; Thayer, Julian F.; Fischer, Joachim E. (Psychosomatic medicine, 2011)
Objective: To assess associations between the main, nonlinear, and interactive effects of the demand-control-support (DCS) model and the cortisol/dehydroepiandrosterone sulfate (DHEA-S) ratio, a biomarker of psychophysical well-being. Methods: Subjects were 596 employees from all occupational levels of a German airplane manufacturing plant. Multiple regression models controlling for age and gender were computed separately for employees with (n = 103) and without (n = 493) management responsibilities. Results: Among employees without management responsibilities, the dimensions of the DCS model did not predict the cortisol/DHEA-S ratio. In contrast, among employees with management responsibilities, both linear and nonlinear job demand effects explained a substantial fraction of the cortisol/DHEA-S variance. Increasing levels of job demands were associated with decreasing cortisol/DHEA-S ratios (linear effect) with the quartile of moderately high levels of job demands representing an optimal level. Furthermore, we observed a significant nonlinear effect with job control and a significant interaction between job demands and job control among employees with management responsibilities. These results suggest a beneficial effect associated with moderate levels of job control. This may be due to a buffering effect against adverse levels of job demands (interactive effect) and the independent association with decreased cortisol/DHEA-S ratios (nonlinear effect). Conclusion: This is the first study that provides evidence that the DCS model is associated with the cortisol/DHEA-S ratio. Among employees with management responsibilities, moderate levels of job control may help managers to cope effectively with job demands and may induce a favorable cortisol/DHEA-S ratio. DCS = demand-control-support; DHEA = dehydroepiandrosterone; DHEA-S = dehydroepiandrosterone sulfate; JCQ = Job Content Questionnaire; MP = management personnel; NMP = nonmanagement personnel; SALSA = salutogenic subjective work analysis.
Gesehen am 05.07.2023
Zur Veröffentlichung eingereicht am 27. April 2010; Überarbeitung eingegangen am 6. September 2010